2012
DOI: 10.1021/ma202481t
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Piezoelectricity of Nanoimprinted Sub-20 nm Poly(vinylidene fluoride–trifluoroethylene) Copolymer Nanograss

Abstract: In this paper, sub-20 nm ferroelectric PVDF–TrFE copolymer nanograss structures with aspect ratios up to 8.9 were developed. This study demonstrated sub-20 nm PVDF–TrFE nanograss structures that are nanoimprinted using a silicon nanograss mold in a single step. Vertically oriented PVDF–TrFE nanopillars were poled using the developed flip-stacking poling method. According to the PFM measurements, the piezoelectricity of flat thin films fabricated in this work reaches 14.0 pm/V. The maximum output voltage of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 27 publications
2
59
0
Order By: Relevance
“…Moreover, a high piezoelectric coefficient of À72 pC/N for P(VDF-TrFe) nanowires was reported by Hong et al [24], this can be explained by the relationship between the thickness and the crystallization. A very weak vertical displacement was obtained with the unpoled device which highlights the necessity to initially pole the P(VDF-TrFe) film in order to initiate the piezoelectric effect in the device by aligning the dipoles.…”
Section: Indirect Piezoelectric Effectmentioning
confidence: 81%
“…Moreover, a high piezoelectric coefficient of À72 pC/N for P(VDF-TrFe) nanowires was reported by Hong et al [24], this can be explained by the relationship between the thickness and the crystallization. A very weak vertical displacement was obtained with the unpoled device which highlights the necessity to initially pole the P(VDF-TrFe) film in order to initiate the piezoelectric effect in the device by aligning the dipoles.…”
Section: Indirect Piezoelectric Effectmentioning
confidence: 81%
“…Co-polymers of PVDF where some of the hydrogen atoms are replaced with fluorine atoms are more likely to crystallise in a polar phase due to steric factors. Even then, it has been reported that electrically poled P(VDF-TrFE) nanowire arrays could have over 10 times higher piezoelectric coefficients than normal P(VDF-TrFE) thin films undergoing the same treatment [25]. More recently, nanowire synthesis approaches making use of a nanoconfinement growth effect have been found to be more likely to result in so-called 'selfpoled' β phase NWs [21,26], mostly observed, for example, in template-assisted growth whereby polymer NWs are grown within nanoporous templates by infiltration from solution or melt, and where the resulting NWs do not require external electrical poling in order to exhibit piezoelectric behaviour.…”
Section: Piezoelectric Polymersmentioning
confidence: 99%
“…[27][28][29][30] In order to produce polymer nanostructures, hot embossing through a mold is applied in the pre-mentioned fabrication techniques. During the hot embossing procedure, the system is heated above the glass transition temperature of the polymer and a desired pressure is applied.…”
Section: -11mentioning
confidence: 99%